2021
DOI: 10.1186/s40168-021-01045-6
|View full text |Cite|
|
Sign up to set email alerts
|

Niche partitioning in the Rimicaris exoculata holobiont: the case of the first symbiotic Zetaproteobacteria

Abstract: Background Free-living and symbiotic chemosynthetic microbial communities support primary production and higher trophic levels in deep-sea hydrothermal vents. The shrimp Rimicaris exoculata, which dominates animal communities along the Mid-Atlantic Ridge, houses a complex bacterial community in its enlarged cephalothorax. The dominant bacteria present are from the taxonomic groups Campylobacteria, Desulfobulbia (formerly Deltaproteobacteria), Alphaproteobacteria, Gammaproteobacteria, and some r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 87 publications
2
44
0
Order By: Relevance
“…6 C). Although microbes are highly functionally redundant [ 58 , 59 ], the massive loss of microbial species, especially rare microbial species, which play a key role in maintaining the microbial functional pool [ 60 ], may also result in the functional loss [ 61 , 62 ]. Consequently, the significant decrease in the microbial biodiversity may suppress microbiome functional potential during continuous cropping.…”
Section: Discussionmentioning
confidence: 99%
“…6 C). Although microbes are highly functionally redundant [ 58 , 59 ], the massive loss of microbial species, especially rare microbial species, which play a key role in maintaining the microbial functional pool [ 60 ], may also result in the functional loss [ 61 , 62 ]. Consequently, the significant decrease in the microbial biodiversity may suppress microbiome functional potential during continuous cropping.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids and stable carbon isotope analyses of R. exoculata indicated that these animals possess a high level of polyunsaturated fatty acids, which can be mobilized to enable growth and maturation of the vent shrimp at a suitable site ( Pond et al, 2000 ). Previous studies have shown that R. exoculata harbors two symbioses: epibiotic communities located at branchiostegites, including a wide diversity of Epsilon-, Gamma-, Alpha-, Beta-, Delta-, Zetaproteobacteria, and Bacteroidetes ( Zbinden et al, 2008 ; Petersen et al, 2010 ; Hügler et al, 2011 ; Guri et al, 2012 ; Jan et al, 2014 ; Cambon-Bonavita et al, 2021 ), and bacterial communities colonized in guts, which are composed of Deferribacteres, Mollicutes, Campylobacteria, and, to a lesser extent, Gammaproteobacteria ( Zbinden and Cambon-Bonavita, 2003 ; Durand et al, 2010 , 2015 ). These results are consistent with the intestinal microflora of R. kairei from the CIR in this study, which is also mainly composed of Deferribacteres, Mollicutes, and Campylobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The best research example of alvinocaridid species is Rimicaris exoculata from the Mid Atlantic Ridge. Recent studies have demonstrated that R. exoculata epibiotic communities consist of two major groups, Campylobacteria (previously Epsilonproteobacteria) and Gammaproteobacteria, and lower abundances of Deltaproteobacteria, Alphaproteobacteria, Zetaproteobacteria, Betaproteobacteria, and Bacteroidetes ( Zbinden et al, 2008 ; Petersen et al, 2010 ; Hügler et al, 2011 ; Guri et al, 2012 ; Jan et al, 2014 ; Cambon-Bonavita et al, 2021 ). It has been evidenced that the chemosynthetic ectosymbionts of R. exoculata can directly transfer nutrients to the host ( Ponsard et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%